1998
DOI: 10.7863/jum.1998.17.5.327
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic diagnosis of trisomy 18: is it practical in the early second trimester?

Abstract: The objective of this paper was to determine the rate of prenatal detection of ultrasonographic abnormalities in fetuses with trisomy 18 during the early second trimester. Our prenatal diagnosis database (encompassing January 1987 to June 1996) was searched for all patients referred for prenatal genetic evaluation between 14 and 22 weeks of gestation and who were found to have a fetus with a trisomy 18 karyotype. The sonographic reports and films were evaluated for the presence or absence of fetal anatomic abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
34
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 21 publications
(19 reference statements)
3
34
1
Order By: Relevance
“…Previously published reports detailing the sonographic findings with trisomy 18 show that, although choroid plexus cysts are seen frequently, most are present with other sonographic findings. [5][6][7][8][9][10][11][12][13] In the 223 fetuses from these combined series that had second-trimester sonograms, isolated choroid plexus cysts were not a common finding (6.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published reports detailing the sonographic findings with trisomy 18 show that, although choroid plexus cysts are seen frequently, most are present with other sonographic findings. [5][6][7][8][9][10][11][12][13] In the 223 fetuses from these combined series that had second-trimester sonograms, isolated choroid plexus cysts were not a common finding (6.7%).…”
Section: Discussionmentioning
confidence: 99%
“…They are seen in up to half of second-trimester fetuses and are often found with other anomalies. [3][4][5][6][7][8][9][10][11][12][13] In the nearly 2 decades since the initial report by Chudleigh et al, 1 a large volume of literature has been published regarding the sonographic detection of choroid plexus cysts in the second trimester. Despite this, a consensus of opinion has yet to be reached on the genetic significance and appropriate management when these cysts are detected as an isolated finding.…”
mentioning
confidence: 99%
“…Three of the fetuses had no sonographic findings at all; however, these examinations were performed between 16 and 17 weeks. 13 In examining fetuses with trisomy 18 during the early second trimester only, Shields et al 4 found that most, but not all (86%; 30 of 35) fetuses had 1 or more detected abnormalities on sonography, with a mean number of abnormalities per fetus of 3 (range, 0-6). Salihu et al 6 found that of their 11 cases of trisomy 18, only 64% had prenatally detected sonographic anomalies, with polyhydramnios (n = 4) being the most commonly seen abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…Only 2 studies provided descriptions about the content of the sonographic examinations in detecting trisomy 18. 4,7 In addition, all previous studies have found that 64% to 97% of fetuses with trisomy 18 have 1 or more detectable abnormalities on sonography.…”
mentioning
confidence: 99%
See 1 more Smart Citation